2022
DOI: 10.7554/elife.78823
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of suspended cells measured with shear flow deformation cytometry

Abstract: Numerous cell functions are accompanied by phenotypic changes in viscoelastic properties, and measuring them can help elucidate higher-level cellular functions in health and disease. We present a high-throughput, simple and low-cost microfluidic method for quantitatively measuring the elastic (storage) and viscous (loss) modulus of individual cells. Cells are suspended in a high-viscosity fluid and are pumped with high pressure through a 5.8 cm long and 200 μm wide microfluidic channel. The fluid shear stress … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…This is in agreement with previous observation of increased cell stiffness under higher deformation frequency. 39 This hypothesis supports the finding that high strain rate in devices without gutters resulted in almost 100% delivery efficiency. We related this volume exchange driving force to the ratio of cell elasticity and viscosity using the Erickson's number.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in agreement with previous observation of increased cell stiffness under higher deformation frequency. 39 This hypothesis supports the finding that high strain rate in devices without gutters resulted in almost 100% delivery efficiency. We related this volume exchange driving force to the ratio of cell elasticity and viscosity using the Erickson's number.…”
Section: Discussionsupporting
confidence: 80%
“…The increase in the measured elastic modulus is consistent with a transition to a viscoelastic cytoplasm. 39 We noticed a sub-linear relation between the increase in stiffness and increase in strain rate. We also observed a linear change in cell relaxation rate with the compression rate (Fig.…”
Section: Stain Rate and Cell Viscous Relaxation Rate Determines Effic...mentioning
confidence: 78%
“…Force application techniques actively deform the sample to probe its mechanical response. These include, among others, AFM, 15,51 nanoindenters, 52,53 acoustic, 54 magnetic 55,56 and optical tweezers (OTs), 57 optical stretchers, 58 deformation cytometry (DC) 59,60 and the biomembrane force probe (BFP) 61 . Instead, force sensing techniques specialize in detecting the forces exerted by cells.…”
Section: Measurements and Applications Of Mechanical Biomarkersmentioning
confidence: 99%
“…Even more challenging is to find agreement in sample characterization across techniques of different nature, where force values are extracted from different mathematical approximations and the stress and deformation scales can be substantially different. While some works provide excellent agreement when viscoelastic parameters were compared across different mechanical techniques, 59 other studies reported differences of up to three orders of magnitude 70 . The study by Wu co‐workers specifically discussed how the mathematical models across techniques can notably change the values obtained on the sample.…”
Section: Challenges Of Mechanical Biomarkersmentioning
confidence: 99%
“…Here, we show that this simple approach, while being correct in its order of magnitude, hides a good amount of the more complex features of intracellular stress. To illustrate this, we apply the theory of Roscoe [49] for a cell in linear shear flow, which accurately describes cell behavior in our numerical simulations (see section II C 4) and in microchannel experiments [69], provided that the cell does not flow in the channel center where the shear rate approaches zero. Inside a flowing cell, two qualitatively different kinds of stress arise.…”
Section: Nozzle Exitmentioning
confidence: 99%